Multivariate GARCH to Measure Volatility Transmission Between Oil and Food Markets - Farah ELIAS , ELHANNANI; BOUSSALEM, Aboubakeur; BELGHALEM, hala (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(--scale-factor)*127.58px); top: calc(var(--scale-factor)*361.99px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.968627);" role="presentation">The movements in the global food prices have been of large interest to the different states <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*376.51px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.931721);" role="presentation">because of the challenging effects on their macroecono<span dir="ltr" style="left: calc(var(--scale-factor)*351.55px); top: calc(var(--scale-factor)*376.51px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.930757);" role="presentation">mic indicators. The causes beyond the large <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.906039);" role="presentation">swings <span dir="ltr" style="left: calc(var(--scale-factor)*137.53px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(1.00504);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*153.83px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.881762);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*175.05px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.93424);" role="presentation">global <span dir="ltr" style="left: calc(var(--scale-factor)*210.30px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.932415);" role="presentation">food <span dir="ltr" style="left: calc(var(--scale-factor)*238.01px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.904135);" role="presentation">market <span dir="ltr" style="left: calc(var(--scale-factor)*276.26px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.84806);" role="presentation">are <span dir="ltr" style="left: calc(var(--scale-factor)*297.48px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.874763);" role="presentation">several <span dir="ltr" style="left: calc(var(--scale-factor)*336.33px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.992186);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*352.52px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.955731);" role="presentation">which <span dir="ltr" style="left: calc(var(--scale-factor)*387.18px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.908394);" role="presentation">we <span dir="ltr" style="left: calc(var(--scale-factor)*407.68px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(1.00352);" role="presentation">find <span dir="ltr" style="left: calc(var(--scale-factor)*433.21px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.93598);" role="presentation">globalization <span dir="ltr" style="left: calc(var(--scale-factor)*498.33px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.865459);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*521.95px); top: calc(var(--scale-factor)*391.03px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.900864);" role="presentation">market <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*405.55px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.911014);" role="presentation">interrelationship as one of the most important causes of the recent uprising volatility in this market. <span dir="ltr" style="left: calc(var(--scale-factor)*127.58px); top: calc(var(--scale-factor)*426.19px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.962789);" role="presentation">This paper highlights <span dir="ltr" style="left: calc(var(--scale-factor)*230.81px); top: calc(var(--scale-factor)*426.19px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.994846);" role="presentation">the latter issue and analyzes the role of the volatility existing in the <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*440.71px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.958012);" role="presentation">international oil market in driving the global food prices fluctuations. To do so, a bivariate GARCH <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*455.23px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(1.00748);" role="presentation">model is used to show the volatility spillover between oil and food markets. A di<span dir="ltr" style="left: calc(var(--scale-factor)*488.62px); top: calc(var(--scale-factor)*455.23px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.978064);" role="presentation">agonal BEKK <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*469.77px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.955365);" role="presentation">specification shows evidence of a link between volatilities in the returns of oil prices and weighted <span dir="ltr" style="left: calc(var(--scale-factor)*99.26px); top: calc(var(--scale-factor)*484.41px); font-size: calc(var(--scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.914274);" role="presentation">index of a set of important food commodities prices.